2016
DOI: 10.22146/agroekonomi.17269
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Marketing Mix and Sales Performance of “Industri Hilir Teh Walini” Product

Abstract: This research as a case study in "Industri Hilir Teh Walini" aimed to: (1) INTISARIPenelitian ini sebagai sebuah studi kasus di "Industri Hilir Walini" bertujuan untuk: (1) mendeskripsikan strategi bauran pemasaran, (2) menguji pengaruh strategi bauran pemasaran terhadap penjualan, (3) mengatahui performa penjualan produk, (4) meramalkan permintaan mendatang dari produk-produk utama, dan (5) menyelidiki kekuatan, kelemahan, peluang, dan ancaman (SWOT). Penjelasan deskriptif, analisis linear berganda, analis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Business realize mark of the marketing strategy implemented blessing competition this. Marketing mix is element from plan marketing this (Oktaviyanti et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Business realize mark of the marketing strategy implemented blessing competition this. Marketing mix is element from plan marketing this (Oktaviyanti et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in their analysis of marketing mix and sales performance, Oktaviyanti et al (2015) found a relationship between these variables, and in their research on the effect of marketing strategies on the performance of SMEs in Cote d'Ivoire, Ardjouman and Asma (2015) established that marketing management strategies have a significant influence on SME performance. This is also in agreement with Kariithi's (2015) study that found marketing strategies influenced the growth and performance of SMEs that operate air travel agencies.…”
Section: Marketing MIX Strategies and Sales Performancementioning
confidence: 99%